Impact of Covid-19 on Mental Health and Treatment Compliance in Psoriasis Patients - Waqar Malik, Wajiha Malik, Sadaf Malik, Jauhar Mumtaz Khan, Zeeshan Haroon, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was designed to determine the impact of COVID-19 on treatment compliance and mental health (anxiety and depression) in psoriasis patients. Methods: A descriptive cross-sectional study was undertaken in the Department of Dermatology at York teaching Hospital from April to August 2020. One hundred and eleven patients diagnosed with psoriasis were asked to complete a questionnaire (HADS). Patients were also asked about their compliance or self-modifications in their treatment regime due to fear of Covid-19. Using SPSS version 26.0 all of the collected data was analysed together. Results: 40 patients (36.03%) had depression and 52 patients (46.84%) anxiety on the basis of their HADS score. Twenty patients (18.01%) stopped treatment due to concerns regarding COVID-19. Prevalence of anxiety was more in female patients and those on traditional immuno-suppressants as compared to biological treatment or those receiving topical treatment only. Conclusion: Depression and anxiety are common in patients with psoriasis. Female patients and those on systemic medications are worse affected compared to patients on topical treatment or those receiving phototherapy. Fear of COVID-19 has led to 18% of patients self-stopping their treatment altogether.